Experimental Study of Awash Soil under Static and Cyclic Shear Loading - Tigistu Abu Arficho; Argaw Asha Ashango (Advances in Civil Engineering)
The dynamic soil properties (shear modulus and damping ratio) are of great importance for the analysis and design of geotechnical structures subjected to dynamic loads such as earthquake. Cyclic simple shear tests were conducted to study the variation of shear modulus and damping ratio with a different number of factors for strain amplitudes of 0.01%, 0.1%, 1%, 2.5%, and 5% and for a frequency of 1 Hz at an axial stress of 150 kPa, 275 kPa, and 400 kPa. The result shows that the damping ratio decreases with an increase in confining pressure at different cyclic shear strains. The shear modulus increases with an increase in the void ratio at different cyclic shear strains. The damping ratio increases with a decrease in soil plasticity. The obtained values of shear modules were in the ranges of 0.292 MPa to 15.998 MPa and the damping ratio values from 0.146% to 30.851%. In concluding the major influencing factors that affect the dynamic properties of soils are confining pressure, void ratio, shear strain amplitude, and soil plasticity.